2007
DOI: 10.1158/1055-9965.epi-07-0210
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of the Carcinogen 4-(Methylnitrosamino)-1-(3-Pyridyl)-1-Butanone in Sidestream Cigarette Smoke Increase after Release into Indoor Air: Results from Unpublished Tobacco Industry Research

Abstract: Research has shown that the toxicity of sidestream cigarette smoke, the primary constituent of secondhand smoke, increases over time. To find potential mechanisms that would explain the increase in sidestream smoke toxicity over time,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 33 publications
3
48
0
1
Order By: Relevance
“…In addition, NNK levels increase as SHS ages, presumably related to the reaction of tobacco-specific alkaloid nicotine with nitric oxide in SHS (Schick & Glantz, 2007;Sleiman et al, 2010). Consistent with these changes in the composition of SHS over time, we recently reported that cotinine measurement leads to an underestimation of exposure to NNK from SHS compared with active smoking (N. Benowitz et al, 2010).…”
mentioning
confidence: 60%
“…In addition, NNK levels increase as SHS ages, presumably related to the reaction of tobacco-specific alkaloid nicotine with nitric oxide in SHS (Schick & Glantz, 2007;Sleiman et al, 2010). Consistent with these changes in the composition of SHS over time, we recently reported that cotinine measurement leads to an underestimation of exposure to NNK from SHS compared with active smoking (N. Benowitz et al, 2010).…”
mentioning
confidence: 60%
“…Given the low volatility of TSNAs and the high levels of nicotine typically found in environments contaminated with tobacco smoke, these carcinogens can persist indoors (42) and on the human envelope. Because of their frequent contact with surfaces and dust, infants and children are particularly at risk.…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence, from our laboratory and others, has shown that SHS undergoes numerous chemical and physical changes after it is released into the air. Nicotine and other semivolatile organic compounds in smoke adsorb to surfaces where they can react with oxidant gases present in SHS and ambient air to form new chemical compounds (Singer et al 2002(Singer et al , 2003Destaillats et al 2006;Schick and Glantz 2007;Petrick et al 2011). …”
mentioning
confidence: 99%